Session 1, Panel 2, Campbell, Cindy. Storytelling, Education and Children - Cindy Campbell. - Jarvis, Dale (2010)
Cindy Campbell speaking at the 18th Annual Conference of Storytellers of Canada-Conteurs du Canada.